(untitled) (Journal of Educational Sciences, 2022)
The necessity to make changes in foreign language teaching has come about because of the worldwide coronavirus pandemic. This in turn has led foreign language teaching into a new stage of development, with a focus placed on online learning. The relevance of our article is determined by the educational process outcome. Competencies rather than knowledge should indicate success in learning. The core values of the education of the future will include the willingness and ability to solve problems, navigate the infinite torrents of information when looking for correct answers, and choosing life-changing paths which develop the inherent individual abilities of each person, as well as showing a genuine interest in one’s favourite occupation, all taking advantage of the latest best practice in research. All this presumes an educational paradigm shift. The Research Aim: to substantiate and collaborate a conceptual basis and methodology, interconnection of subject-process aspects of foreign language content for the phased formation of professional communicative competence as a methodological category specific of digital technologies in a foreign language school, conducting an experimental study in order to support the stated hypothesis. The practical significance of the research consists of developing a methodology for the gradual formation of professional communicative competence using digital technologies and tools, it reflects the criteria and parameter aspects established, combined with the developed typology of exercises. The training toolkit developed as an applied product can be used for educational matters within the university teaching environment. The methodological framework consists of experimental work that took place in the Ablaikhan Kazakh University in accordance with the education program within the discipline, “Language for Special Purposes” for 4th-year undergraduate students. In total 294 such students were involved, allocated to experimental and control groups. The experimental study included both variable and non-variable conditions. The variable conditions of the study of experimental and control groups are determined as: - the methodology of the formation of professional communicative competence using digital technologies and tools. Non-variable conditions of the study of experimental and control groups are determined as: - the experiment’s period of time, the number of practical lessons, approximately the same level of language proficiency at the beginning of the experimental study in experimental and control groups, the same assessment forms. Key words: teacher, instructor, student, competence, approach, methods, methodological category, foreign language education, technologies.